Socio-economic impact of Niger Delta Development Commission (NDDC) infrastructural projects in selected communities in IMO State Nigeria - Isidiho, Alphonsus Okpechi; Sabran, Mohammad Shatar (Asian Journal of Humanities and Social Sciences, 2015)
Niger Delta Development Commission (NDDC) is a Commission set up by the Federal Government of Nigeria in 2000 with a mandate to “facilitate the rapid, even and sustainable development of the Niger Delta into a region that is economically prosperous, socially stable, ecologically regenerative and politically peaceful”. This paper is concentrating on the socio-economic impact of the Commission’s projects on roads, water and electricity in Ohaji/Egbema, Oguta and Obowo communities in Imo State Nigeria. There have been lots of Niger Delta Development Commission projects in the Niger Delta Region and Imo state as a state in the NDR has benefitted from these projects right from the inauguration of the Board of NDDC in 2001 till date. Generally, infrastructural projects includes roads, electricity, water, transportation, communication, sewage and most cases such projects are sponsored by the government, corporate bodies and international organizations due to the high financial cost for their execution and secondly because of their great importance to communities’ welfare and development. Hence individuals do not get involved in them because of the high cost and the inability to check the benefits or externalities. Wikipedia defined infrastructure generally as the set of interconnected structural elements that provide a framework supporting an entire structure of development. And in modern time, availability of such elements is used as parameters for assessing the level of development of communities and countries. Most government provides these facilities to check their cost and charges when provided by individuals or companies so as to control the capitalist monopolist tendencies of exorbitant charges and extortion since they are necessities of life. The Niger Delta Region covered by NDDC are the nine states in Nigeria as follows: Delta, Akwa-Ibom, Bayelsa, Cross River, Rivers, Ondo, Imo, Abia and Edo States but this study is concentrating on the communities of Ohaji/Egbema, Obowo and Oguta in Imo state. A mixed method research was conducted and a survey design utilized. Hence qualitative and quantitative approached were used and four hundred questionnaires were administered, face to face interviews were conducted on nine participants while five telephone interviews were also used on randomly selected participants. The analysis showed that these infrastructural projects had a lot of social and economic impact on the communities, hence Government and NDDC should be encouraged to construct more of these projects not only in the communities under study but also in other communities.